Down-regulation of toll-like receptor TLR4 is associated with HPV DNA integration in penile carcinoma - Damasdi, Miklos; Kovacs, Gyula (Anticancer research, 2017)
Background/Aim: Development of penile cancers is attributed to HPV-related carcinogenesis. Our aim was to analyze HPV positivity and TLR4, p16ink4a and p53 expression. Materials and Methods: HPV presence was assessed with virus-specific TaqMan PCR and HPV Genotyping Test in 31 penile cancers. Immunohistochemistry was carried out on tissue microarray. Results: TLR4 expression was detected in 4 of the 16 HPV positive and 13 of the 15 HPV negative tumors. We found a significant inverse correlation between HPV positivity and TLR4 expression (p=0.0006). Ten of the 16 HPV-positive but none of the 15 HPV-negative tumors expressed p16INK4a. A significant correlation was seen between p53 expression and lack of HPV DNA (p=0.0191) as well as between TLR4 and p53 expression (p=0.0198) in penile cancers. Conclusion: Our findings suggest a protective role of TLR4 expression against HPV DNA integration and the viral and non-viral carcinogenesis of penile cancer.